Enzymatic Excision of Uracil Residues in Nucleosomes Depends on Local DNA Structure and Dynamics - Ye, Yu (2012)
The excision of uracil bases from DNA is accomplished by the enzyme uracil DNA glycosylase (UNG). Recognition of uracil bases in free DNA is facilitated by uracil base pair dynamics, but it is not known whether this same mechanistic feature is relevant for detection and excision of uracil residues embedded in nucleosomes. Here we investigate this question using nucleosome core particles (NCPs) generated from X. laevis histones and the high-affinity “Widom 601” positioning sequence. The reactivity of uracil residues in NCPs under steady-state multiple turnover conditions was generally decreased as compared to free 601 DNA, mostly due to anticipated steric effects of histones. However, some sites in NCPs had equal or even greater reactivity than free DNA, and the observed reactivities were not readily explained by simple steric considerations, or by global DNA unwrapping models for nucleosome invasion. In particular, some reactive uracils were found in occluded positions, while some unreactive uracils were found in exposed positions. One feature of many exposed reactive sites is a wide DNA minor groove, which allows penetration of a key active site loop of the enzyme. In single-turnover kinetic measurements, multi-phasic reaction kinetics were observed for several uracil sites, where each kinetic transient was independent of the UNG concentration. These kinetic measurements, and supporting structural analyses, support a mechanism where some uracils are transiently exposed to UNG by local, rate-limiting nucleosome conformational dynamics, followed by rapid trapping of the exposed state by the enzyme. We present structural models and plausible reaction mechanisms for the reaction of UNG at three distinct uracil sites in the NCP.